Multipath TCP. - PAASCH, CHRISTOPH; BONAVENTURE, OLIVIER (Communications of the ACM, 2014)
The article presents information on the problems association with one the early design decisions of Transmission Control Protocol (TCP). The separation between the Internet Protocol and TCP is not complete though they are separate protocols. Seberal researchers have proposed solutions to the problem and examples of such solutions are Mobile IP and Host Identity Protocol (HIP). Multipath TCP is an extension of TCP designed by collective work of several researchers. MPTCPS can be benificial for smartphones and data centers.